DETERMINATION OF MINERALS IN LAVANDULA STOECHAS L. SUBSP. CARIENSIS (BOISS.) ROZEIRA BY X-RAY FLUORESCENCE SPECTROSCOPY - Hüsniye, Kayalar; Sinem, Yılmaz Zehra; Cenk, Durmuşkahya; Ümit, Toktaş (Universal Journal of Pharmaceutical Research, 2023)
Background and objective: Medicinal herbs are sources of bioactive plant secondary metabolites such as phenolic acids, flavonoids, iridoids, tannins, anthracenes, alkaloids, terpenes. Herbs and herbal extracts are important sources for minerals that can create health effects in human diet. The infusion and decoction prepared from Lavandula stoechas L., subsp. cariensis known as Karabaşotu in Turkey, are used in traditional medicine. The objective of the present work was to comparatively determine the mineral content of dried aerial parts L. stoeachas L. subsp. cariensis and its water extract which is prepared by 2% infusion. Methods: The aerial parts of Lavandula stoechas L., were air-dried and grounded. 2% infusion was prepared by distilled water and water was evaporated until dryness. The water extract and the plant powder were analyzed for heavy metals and trace elements by Spectro-IQ II instrument. Results: The analyzed samples differed significantly in terms of mineral contents. The powdered aerial parts of L. stoechas L. subsp. cariensis and its water extract are characterized by high contents of potassium, calcium, sodium, chlorine, phosphorous and magnesium. Iron in powdered plant material (576.6 ppm) was found to be almost ten times higher than the water extract (51.7 ppm). Microelements such as copper (78.8 ppm) and zinc (3169 ppm) accumulated at higher levels in the water extract of L. stoechas L. subsp. cariensis. Conclusion: The mineral content of the water extract and the powdered aerial parts of L. stoechas L. subsp. cariensis are quantitatively determined by X-ray fluorescence spectroscopy for the first time. L. stoechas L. subsp. cariensis collected from other regions of Turkey will be comparatively analyzed by XRF spectrometry in our further studies. Peer Review History: Received: 5 August 2023; Revised: 10 September; Accepted: 27 October; Available online: 15 November 2023 Academic Editor: Dr. Gehan Fawzy Abdel Raoof Kandeel , Pharmacognosy Department, National Research Centre, Dokki, 12622, Giza, Egypt, gehankandeel9@yahoo.com Reviewers: Dr. Sangeetha Arullappan, Universiti Tunku Abdul Rahman, Malaysia, sangeetha@utar.edu.my Ahmad Najib, Universitas Muslim Indonesia, Makassar, Indonesia, ahmad.najib@umi.ac.id